Estudo das propriedades estruturais e de transporte dos compósitos magneto-dielétricos : [(Fe5/8Cr3/8)2O3]X-[(Fe1/4Cu3/8Ti3/8)2O3]100-X - Rocha, Hélio Henrique Barbosa (2006)
The processing in laboratorial scale of solid solutions, derived from Fe2O3/CuO/TiO2 and Fe2O3/Cr2O3 systems, of their composites, and the study of the structural and transport properties establish the main theme of the work. The ferrimagnetic garnets arouse great interest in view of their use in devices applicable to telecommunication systems, in the microwaves, above all, in function of appropriate dielectric and magnetic properties. Due to stoichiometric resemblance, and with the purpose of obtaining materials with similar properties, two magneto-dielectric media were elaborated: (Fe1=4Cu3=8Ti3=8)2O3, a copper-iron titanate, and (Fe5=8Cr3=8)2O3, a particular oxide of iron and chrome. These substitutional solid solutions were synthesized by solid state reaction technique. The processing advanced involving mechanic and thermal treatments. Were prepared specimens powdered and sintered. The crystalline structure of the specimens was identified by X-ray diffraction. The X-ray diffraction data were refined by the employment of the Rietveld’s method. Use of the Mössbauer spectroscopy was made to accomplish the inspection of the iron present in the crystalline structure. The morphology of the specimens, disposed as rigid cylindrical pieces, was explored by means of Scanning Electron Microscopy, assisted by EDX, for elementary chemical analysis. Through dielectric spectroscopy, the dielectric properties relative dielectric permittivity and dielectric loss factor and the transport property electric conductivity were investigated. The dielectric and transport properties were analyzed in function of the frequency, at room temperature, in the range between 100 Hz and 40 MHz. Of the X-ray diffraction data, in addition to the identification of the examined materials, were extracted, after structural refinement, crystallographic information, in the case of the individual solid solutions, and their quantification, for the composites. For the Mössbauer spectroscopy, were confirmed the state of oxidation of iron presents in the analyzed materials, the geometry of the crystalline sites in which it is present, the magnetic nature of the samples, and their probable ordering, in addition to the quantification consummated in function of the amount of iron present in the composites. The morphology of the materials was, in general, characterized by the diversity of forms and sizes of the grains, as well as its arrangement in the observed samples. The elementary chemical analysis supplied quantitative results concerning the elements present in the investigated samples. For the response observed in the range of frequency, a dispersion region, characteristic of the dipolar polarization mechanism, was evidenced. The results of the dielectric properties for the synthesized phases were shown partially antagonistic: the phase IB100 presented the largest relative dielectric permittivity, however, larger dielectric loss factor compared to the phase IC100, the one which presented the smallest relative dielectric permittivity among all the investigated materials. For the composites, formed by the random mixture of specific amounts of the two synthesized phases, a non linear behavior was evidenced, so that these do not represent the responses observed for the phases individually. The phase IB100, by virtue of its dielectric constant, is the material with the great potential for applications in high frequencies.